(untitled) (Journal of Education and Development, 2018)
The purpose of this study was to explore families’ support and influence on the educational performance of students on a faith-based campus in northern Indiana, USA. The study answered the following research question: How does families’ support influence college students’ educational performance? This research question was developed after reviewing the literature and coming to the realization that there is little research on families’ influence role in college students’ academic performance. The data was collected through in-depth interviews with 12 students who resided at the college campus. Themes recognized within the study were used to discuss families’ role in students’ academic performance. Considering the families’ role in students’ everyday life and the background support is vital to their educational performance. Themes included: (1) Frequency of contact with family, especially mother; (2) Levels of parental financial involvement; (3) Independence from family; (4) Siblings’ influence on academics; (5) Parents’ spiritual involvement; and (6) Parents’ educational background.